PLANNING IN ISLAMIC EDUCATION MANAGEMENT ACCORDING TO THE QURAN AND HADITH - Mei Utari, Hanny; Fauji , Imam (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to examine the concept of planning in Islamic educational management based on evidence from the Qur'an and Hadith. It seeks to explore its application in modern Islamic education systems to enhance effectiveness, systematic implementation, and alignment with the primary objectives of Islamic education—producing generations with faith, knowledge, and noble characte. Method: The research employs a qualitative approach, utilizing content analysis of relevant Qur'anic verses and Hadith. The study highlights key principles and practices of planning derived from Islamic teachings and their strategic application in the context of contemporary Islamic educational management. Results: Findings reveal that Islamic planning is deeply rooted in the Qur'an and Hadith, emphasizing strategic, anticipatory thinking and systematic steps to achieve educational objectives aligned with sharia principles. For instance, Qur'an Surah Al-Hasyr (59:18) underscores the importance of foresight and preparation. The Prophet Muhammad SAW demonstrated planning practices in his strategies for da'wah and community education management, which remain relevant in addressing modern educational challenges. Novelty: This study uniquely integrates classical Islamic texts with modern educational management principles, providing a systematic framework for implementing Islamic values in contemporary educational planning. It contributes to a deeper understanding of how Islamic teachings can enhance the strategic and operational effectiveness of modern Islamic education systems.